Answer:
4 x^3 - 3 x^2
Step-by-step explanation:
Expand the following:
x^2 (4 x - 3)
x^2 (4 x - 3) = x^2×4 x + x^2 (-3):
4 x^2 x - 3 x^2
x^2×4 x = x^(2 + 1)×4:
4 x^(2 + 1) - 3 x^2
2 + 1 = 3:
Answer: 4 x^3 - 3 x^2
Answer:
Step-by-step explanation:
I got you kiddo
You do 2*d - 2*5 = 8 which is 2d-10=8 ------> 2d=8+10 and you do d=18/2 which d = 9
Answer:
$2,543.84 is your answer.
Step-by-step explanation:
What you do first is you have to figure out the 5.99% interest rate.
150 x 5.99 = 8.99
150 + 8.99 = $158.99
Now multiply that by 16
158.99 x 16 = $2,543.84 is your answer.
Answer:
x^2 + y^2 = 100
Step-by-step explanation:
The general form of the equation of a circle is
(x-h)^2+(y-k)^2 = r^2
where (h,k) is the center and r is the radius
(x-0)^2+ (y-0)^2 = 10^2
x^2 + y^2 = 100
-5, because subtracting a negative is the same as adding a positive, which will bring -9 up to -5